18F‐Labeling of Sensitive Biomolecules for Positron Emission Tomography. Issue 62 (1st September 2017) - Krishnan, Hema S.; Ma, Longle; Vasdev, Neil; Liang, Steven H.
Abstract: Positron emission tomography (PET) imaging study of fluorine‐18 labeled biomolecules is an emerging and rapidly growing area for preclinical and clinical research. The present review focuses on recent advances in radiochemical methods for incorporating fluorine‐18 into biomolecules via "direct" or "indirect" bioconjugation. Recently developed prosthetic groups and pre‐targeting strategies, as well as representative examples in 18 F‐labeling of biomolecules in PET imaging research studies are highlighted. Abstract : In this review, we focus on recent progress in 18 F‐radiochemical methods for labeling biomolecules, including direct/indirect methods, prosthetic groups, click chemistry and pre‐targeting strategies for positron emission tomography (PET). Representative examples of 18 F‐labeling of biomolecules in PET imaging studies are also highlighted.